Mendorong Transformasi Digital UMKM Desa Ciherang: Siap Menghadapi 5.0 dengan Inovasi Pembuatan NIB dan Penerapan Digital Marketing - Ramdhan, Anggal Noor; Marwah, Suci; Yuliani, Selfi; Nurfadillah, Riski; Azzahra, Naftali; Wachdijono, Wachdijono (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
The Industrial Revolution 5.0 requires MSMEs in Ciherang Village to adopt digital technology to remain competitive and able to compete in the global market. This research aims to support MSMEs through assistance in creating a Business Identification Number (NIB) and digital marketing training. The research method includes an initial survey to identify the level of technology utilization by local MSMEs, followed by digital marketing training, use of e-commerce platforms, and NIB registration. As a result, 15 MSMEs succeeded in obtaining NIB, while others began to utilize digital platforms such as Shopee and TikTok to expand their market reach. Even though this training improves the digital skills of business actors, challenges such as uneven internet access, varying technological capabilities, and limitations in using technology independently are still the main obstacles. Therefore, long-term investment in digital infrastructure, increased technological literacy, and ongoing assistance are needed to ensure the sustainability of the digital transformation of MSMEs in Ciherang Village.